PENGEMBANGAN MEDIA ARTICULATE STORYLINE BERBASIS SAINTIFIK PADA TEMA 4 HIDUP BERSIH DAN SEHAT DI KELAS II SD PAB 22 PATUMBAK DELI SERDANG - Windi Tri Andini; Sujarwo Sujarwo (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2025)
This study aims to: (1) To find out how the process of developing Artculate Storyline media based on the Scientific model on theme 4 clean and healthy living can be applied to grade II students of SD Persatuan Amal Bakti 22 Patumbak. (2) To find out how feasible the Artculate Storyline media based on the Scientific model on theme 4 clean and healthy living can be applied to grade II students of SD Persatuan Amal Bakti 22 Patumbak. This study is a type of research and development with reference to the ADDIE model which stands for Analyze, Design, Development, Implementation, Evaluation. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative and quantitative. The results of the validation of the responses of grade II teachers can be seen that the quality of the articulate storyline media on the theme of clean and healthy living gets a percentage of 85%. The results of the assessment validation by media experts get 96% of 13 statements. The results of the assessment validation by material experts get a score of 95% of 10 statements. The results of the student response assessment validation get 95% of 8 statements. The developed articulate storyline can be applied as an initial step for the teaching and learning process in schools, thus the articulate storyline on the theme of clean and healthy living shows very valid or very feasible criteria.